A validated UHPLC‐MS/MS method for determination of TQ‐B3203 in human plasma and its application to a pharmacokinetic study in Chinese patients with advanced solid tumor. Issue 5 (18th January 2021) - Yang, Fen; Zhou, Jun; Bo, Yunhai; Yin, Han; Liu, Xiao Hong; Li, Jian
Abstract: TQ‐B3203 is a new topoisomerase I inhibitor derived from camptothecin. In this paper, a simple and reliable ultra high‐performance liquid chromatography‐tandem mass spectrometric method was developed and validated for determination of TQ‐B3203 in human plasma with TQ‐B3203‐d8 used as the internal standard. Bis(p‐nitrophenyl)phosphate (2 mol/L) was added to ensure the stability of TQ‐B3203 in human plasma. Plasma samples were protein precipitated by methanol and processed samples were chromatographed on an AQUITY BEH C8 column (50 × 2.1 mm, id 1.7 μm) with acetonitrile and water (0.1% formic acid) as the mobile phase. The calibration curves showed good linearity ( R ≥0.99) over the concentration range of 0.5–500 ng/mL. Within‐ and between‐run precision were ≤5.8% and the accuracy was within the range of −8.3 to 14.0%. This method was further successfully applied to a pharmacokinetic study of TQ‐B3203 in Chinese advanced solid cancer patients after administration of TQ‐B3203 liposome injection.